The fundamental role of endothelial cells in hantavirus pathogenesis - Hepojoki, Jussi; Vaheri, Antti; Strandin, Tomas (Frontiers in Microbiology, 2014)
Hantavirus, a genus of rodent- and insectivore-borne viruses in the family Bunyaviridae, is a group of emerging zoonotic pathogens. Hantaviruses cause hemorrhagic fever with renal syndrome (HFRS) and hantavirus cardiopulmonary syndrome (HCPS) in man, often with severe consequences. Vascular leakage is evident in severe hantavirus infections, and increased permeability contributes to the pathogenesis. This review summarizes the current knowledge on hantavirus interactions with endothelial cells, and their effects on the increased vascular permeability.